2014
DOI: 10.1039/c4ob00592a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and characterization of liposome-incorporated adamantyl aminoguanidines

Abstract: A series of mono and bis-aminoguanidinium adamantane derivatives has been synthesized and incorporated into liposomes. They combine two biomedically significant molecules, the adamantane moiety and the guanidinium group. The adamantane moiety possesses the membrane compatible features while the cationic guanidinium subunit was recognized as a favourable structural feature for binding to complementary molecules comprising phosphate groups. The liposome formulations of adamantyl aminoguanidines were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Results from recent work in our laboratory—including the studies of adamantyl tripeptides, adamantyl glycopeptides, and adamantyl guanidines, their incorporation into liposomes and interaction with the liposome bilayer as an artificial biological membrane [ 31 , 32 ]—prompted us to review the use of the adamantyl group in designing new targeted drug delivery systems and their application in drug-membrane interaction studies.…”
Section: Adamantane Derivatives In Liposomesmentioning
confidence: 99%
“…Results from recent work in our laboratory—including the studies of adamantyl tripeptides, adamantyl glycopeptides, and adamantyl guanidines, their incorporation into liposomes and interaction with the liposome bilayer as an artificial biological membrane [ 31 , 32 ]—prompted us to review the use of the adamantyl group in designing new targeted drug delivery systems and their application in drug-membrane interaction studies.…”
Section: Adamantane Derivatives In Liposomesmentioning
confidence: 99%
“…The aggregation of the DPPC liposomes due to the presence of amphiphilic adamantyl compounds has been reported. [38] However, polydispersion of liposomes observed by DLS may partly be due to the aggregation of 1.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Our previous research of biologically active adamantoylated compounds has been focused on their interaction with model biological membrane. [20][21][22] Although the effect of ferrocene on liposome has not been studied intensively, several recent papers have described the application of oxidized ferrocene as an organometallic amphiphile and ferrocene-modified phospholipid in preparation of the redox-modified liposomes. [58,59] They are capable to target cancer cells and selectively trigger the release of incorporated drug using the electrochemical activity of a ferrocene-modified phospholipid.…”
Section: Entrapment Of Adamantyl Ferrocene Derivatives In Liposomesmentioning
confidence: 99%
“…Our previous research of adamantane derivatives of biologically active peptidoglycan fragments has shown their strong interaction with lipid membrane . Furthermore, we have shown that the adamantyl moiety can be employed as an anchor in the lipid bilayer while the polar part of the molecule, a carbohydrate mannose or guanidine residue, is exposed on the liposome surface …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation